Paul's Journeys in 3D The Apostle as Ideal Ancient Traveller - Wilson, Mark W. 1949- (2018)
Travel in Asia Minor during the Roman period was ubiquitous. The apostle Paul is used as a heuristic model of the ideal ancient traveller. His first journey in provincial Galatia- geographical Pamphylia, Pisidia, and Phrygia-is examined, particularly as it relates to suggested routes and time of travel. It will utilise Bekker-Nielsen's pioneering 3D methodology that applies Naismith's rule to produce more objective outcomes. Practical issues related to ancient travel, such as equipment, load, and weather, will also be explored. This investigation will help to refine travel times and itineraries, and thus hopefully produce more accurate Pauline chronologies.
Keywords: Naismith's rule; Paul's first journey; Via Sebaste; ancient travel